2022
DOI: 10.3390/ma15145086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Grain Orientation on Reliability Issues of Sn-Rich Solder Joints

Abstract: Sn-rich solder joints in three-dimensional integrated circuits and their reliability issues, such as the electromigration (EM), thermomigration (TM), and thermomechanical fatigue (TMF), have drawn attention related to their use in electronic packaging. The Sn grain orientation is recognized as playing an important role in reliability issues due to its anisotropic diffusivity, mechanical properties, and coefficient of thermal expansion. This study reviews the effects of the Sn grain orientation on the EM, TM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Void formations can be observed in the following three stages. First, the numerous Cu atoms diffusing into the Sn lattice from the Cu film are via interstitial diffusion, which has a lower energy barrier than vacancy diffusion [36], resulting in rapid Cu diffusion into Sn [37]. This causes considerable vacancies to exit near the Cu site after Cu diffusion into the Sn lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Void formations can be observed in the following three stages. First, the numerous Cu atoms diffusing into the Sn lattice from the Cu film are via interstitial diffusion, which has a lower energy barrier than vacancy diffusion [36], resulting in rapid Cu diffusion into Sn [37]. This causes considerable vacancies to exit near the Cu site after Cu diffusion into the Sn lattice.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, various signal integrity (SI) and power integrity (PI) issues can arise. In particular, when the noise couples to vertical interconnects such as through glass vias (TGVs), the SI/PI can be degraded even more at solder joints and micro-bumps [17,18] underneath TGVs due to dimensional mismatches. Various types of noise sources that can cause power/ground noise in the glass interposer PDN are depicted in Figure 2.…”
Section: Figurementioning
confidence: 99%
“…Arfaei et al 11 reported longer thermal fatigue life for joints containing β-Sn grains with interlaced morphology compared with beachball morphology. Various authors [12][13][14][15] have noted the importance of CTE mismatch at grain boundaries in damage development in multigrain joints, but these have not quantitatively linked the different orientations within joints to the local CTE mismatch and subsequent damage. At the same time, microstructurally motivated models have been developed [16][17][18][19] to investigate microstructural effects on failure mechanisms and damage evolution in joints subject to thermal cycling and/or shear stress.…”
mentioning
confidence: 99%